1993
DOI: 10.12693/aphyspola.83.817
|View full text |Cite
|
Sign up to set email alerts
|

Vibronic Effects in EPR Spectra of (NH4)2Cu(BeF4)2·6H20 Single Crystal

Abstract: Angular variations of the g-factors and linewidth value were recorded at X-band, at room temperature, and at 77 K. The temperature dependence of the g-factors was measured along the principal g-tensor axes in the temperature range from 4.2 K to 300 K. The rigid lattice g-factors at 4.2 K are: g. = 2.428, gy = 2.138, and gx = 2.058. The gx value very slowly increases linearly on heating, whereas gz and gy nonlinearly tend towards their average value. This is a typical behaviour of Cu(II) EPR in Tutton salt crys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…Moreover, still open questions exist in paramagnetic salts with Jahn−Teller active ions, particularly for Cu 2+ in Tutton salt type crystals of general formula M‘ 2 M‘‘(SO 4 ) 2 ·6H 2 O where M‘ = NH 4 , K, Rb, Cs, Tl and M‘‘ = Cu, Zn, Cd, Mg, Co, Ni, Mn. The fluxional behavior of the Cu(H 2 O) 6 2+ octahedra was observed by EPR both in copper(II)-doped diamagnetic Tutton salts and in pure Cu(II) salts. The molecular and crystal structure details and their temperature variations were studied in recent years with increasing accuracy by X-ray and neutron diffraction in hydrogeneous and deuterated salts, and a unified interpretation of the structural and fluxional behavior has recently been proposed …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, still open questions exist in paramagnetic salts with Jahn−Teller active ions, particularly for Cu 2+ in Tutton salt type crystals of general formula M‘ 2 M‘‘(SO 4 ) 2 ·6H 2 O where M‘ = NH 4 , K, Rb, Cs, Tl and M‘‘ = Cu, Zn, Cd, Mg, Co, Ni, Mn. The fluxional behavior of the Cu(H 2 O) 6 2+ octahedra was observed by EPR both in copper(II)-doped diamagnetic Tutton salts and in pure Cu(II) salts. The molecular and crystal structure details and their temperature variations were studied in recent years with increasing accuracy by X-ray and neutron diffraction in hydrogeneous and deuterated salts, and a unified interpretation of the structural and fluxional behavior has recently been proposed …”
Section: Introductionmentioning
confidence: 99%
“…The models assume that the adiabatic potential surface is temperature-independent. This assumption was questioned, and it was suggested that the lattice strains can vary with temperature, producing variations in energy barrier between the wells. ,, …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using this approach, Silver and Getz were able to successfully explain the variation of the g and A Cu tensors in ZKH, finding an energy difference δ 12 = 75 cm –1 between the lowest two valleys . This work was soon followed by similar SG analysis of this fluxation behavior of Cu 2+ (H 2 O) 6 in other Tutton salts ,, and analogues , and found δ 12 values ranging from ∼75 to 300 cm –1 for the magnetically dilute crystals and ∼300 to 500 cm –1 for the pure copper Tutton crystals.…”
Section: Introductionmentioning
confidence: 92%
“…Several of these EPR studies revealed limitations of the SG model with the most apparent being the fact that δ 12 is not constant over the entire temperature range. ,,, In other systems, the tensor variations were not fully predicted, ,, which was initially suggested as due to a non-Boltzmann thermal equilibrium at low temperatures but later also from temperature-dependent changes in the lattice strains. In a few other cases, g min was observed to vary with temperature, , and therefore a three-state SG model was applied. ,, …”
Section: Introductionmentioning
confidence: 99%